Activities and Molecular Mechanisms of Diterpenes, Diterpenoids, and Their Derivatives in Rheumatoid Arthritis. (25th March 2022) - Torequl Islam, Muhammad; Quispe, Cristina; Herrera-Bravo, Jesús; Rahaman, Md. Mizanur; Hossain, Rajib; Sarkar, Chandan; Raihan, Md Abdur; Chowdhury, Md. Mashrur; Uddin, Shaikh Jamal; Shilpi, Jamil A.; Marcelo de Castro e Sousa, João; Melo-Cavalcante, Ana Amélia de Carvalho; et al.
Abstract : Diterpenes and their derivatives have many biological activities, including anti-inflammatory and immunomodulatory effects. To date, several diterpenes, diterpenoids, and their laboratory-derived products have been demonstrated for antiarthritic activities. This study summarizes the literature about diterpenes and their derivatives acting against rheumatoid arthritis (RA) depending on the database reports until 31 August 2021. For this, we have conducted an extensive search in databases such as PubMed, Science Direct, Google Scholar, and Clinicaltrials.gov using specific relevant keywords. The search yielded 2708 published records, among which 48 have been included in this study. The findings offer several potential diterpenes and their derivatives as anti-RA in various test models. Among the diterpenes and their derivatives, andrographolide, triptolide, and tanshinone IIA have been found to exhibit anti-RA activity through diverse pathways. In addition, some important derivatives of triptolide and tanshinone IIA have also been shown to have anti-RA effects. Overall, findings suggest that these substances could reduce arthritis score, downregulate oxidative, proinflammatory, and inflammatory biomarkers, modulate various arthritis pathways, and improve joint destruction and clinical arthritic conditions, signs, symptoms, and physical functions in humans and numerous experimental animals, mainly through cytokine and chemokine as well as several physiological protein interaction pathways. Taken all together, diterpenes, diterpenoids, and their derivatives may be promising tools for RA management.